2017
DOI: 10.17221/172/2016-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Influence of socio-demographic and experiential factors on the attitudes of Croatian veterinary students towards farm animal welfare

Abstract: The aim of this study was to examine the factors influencing the attitudes of veterinary students in Croatia toward farm animal welfare. The survey was carried out at the only faculty of veterinary medicine in Croatia and included students from all years of the integrated undergraduate and graduate study programme. The response rate was 91% (n = 505 subjects). According to the socio-demographic and experiential factors observed, females, students in their initial years of study, younger students with urban bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 42 publications
(61 reference statements)
4
24
0
Order By: Relevance
“…Teaching veterinary students is not just an educational exercise but has a substantial role in the formation and learning of these professionals how to cope with the emotionally difficult aspects of veterinary work, as well as in the development of their attitudes and opinions towards animal welfare as the most important task of each veterinary practitioner [13,21,22]. To our knowledge, the present study is the first one addressing the opinions of Croatian veterinary students towards CA and their welfare.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Teaching veterinary students is not just an educational exercise but has a substantial role in the formation and learning of these professionals how to cope with the emotionally difficult aspects of veterinary work, as well as in the development of their attitudes and opinions towards animal welfare as the most important task of each veterinary practitioner [13,21,22]. To our knowledge, the present study is the first one addressing the opinions of Croatian veterinary students towards CA and their welfare.…”
Section: Discussionmentioning
confidence: 93%
“…Our previous study [12] showed generally concerned attitudes of veterinary students in Croatia towards farm animal welfare. However, upon detailed analysis of their attitudes, it appeared that they did not think rationally about the issue of farm animal welfare, as they might perceive these animals just as food production animals, implying their practical value; this in particular held true for final-year students [13]. Lower attitudes towards animals and their welfare in veterinary students at higher study years were also recorded in other studies [6,[14][15][16].…”
Section: Introductionmentioning
confidence: 89%
“…However, it has been demonstrated that humans may prefer some animal species to others (Serpell, 2004; de la Fuente et al, 2017). Attitudes towards animals are important because they affect how humans validate animal life, how they behave towards animals, or how they treat them (Ostovic et al, 2017). Besides the animal itself, attitudes towards animals may be influenced by many other factors, such as personal and cultural characteristics (Serpell, 2004;Ormandy and Schuppli, 2014;Borgi and Cirulli, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Urban and rural backgrounds also provide a different cultural experience, playing an important role in shaping human attitudes towards animals (Kendall et al, 2006). In urban areas of developed countries, where people typically have no contact with farm animals, companion animals are regularly considered as family members (Ostovic et al, 2017). Moreover, worldwide differences in the attitudes towards animals and their use may be the result of influences of different cultures and legislations, as well as economic opportunities (Phillips et al, 2012;Špinka, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Hands-on experiences with animals are therefore emphasised by most universities in their equine and veterinary science degree programmes [2] to complement theoretical teaching. The importance of practical classes in the curriculum has grown, as most students that now enter animal-based programmes come from an urban background with limited animal experience [9][10][11][12]. Equine practical teaching classes may well be the first occasion for some students to interact with a horse [13,14].…”
Section: Introductionmentioning
confidence: 99%